2017
DOI: 10.1073/pnas.1710354114
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms and structural features of cardiomyopathy-causing troponin T mutants in the tropomyosin overlap region

Abstract: Point mutations in genes encoding sarcomeric proteins are the leading cause of inherited primary cardiomyopathies. Among them are mutations in the gene that encodes cardiac troponin T (TnT). These mutations are clustered in the tropomyosin (Tm) binding region of TnT, TNT1 (residues 80-180). To understand the mechanistic changes caused by pathogenic mutations in the TNT1 region, six hypertrophic cardiomyopathy (HCM) and two dilated cardiomyopathy (DCM) mutants were studied by biochemical approaches. Binding ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 57 publications
8
60
0
Order By: Relevance
“…Previous studies report on the TnT1 domain’s crucial flexibility and its role in regulating Tm positioning for contraction [2830]. Further evidence for the importance of this domain in our study of TnT1 mutations lies in their ability to alter the affinity of troponin complex for Tm [31]. Therefore, we suggest that the most targeted approach to “rescuing” either HCM or DCM phenotype would be to have a mutation within that same domain to counteract manifestation of the disease, probably through TnT1’s flexibility and eventually altered contraction.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Previous studies report on the TnT1 domain’s crucial flexibility and its role in regulating Tm positioning for contraction [2830]. Further evidence for the importance of this domain in our study of TnT1 mutations lies in their ability to alter the affinity of troponin complex for Tm [31]. Therefore, we suggest that the most targeted approach to “rescuing” either HCM or DCM phenotype would be to have a mutation within that same domain to counteract manifestation of the disease, probably through TnT1’s flexibility and eventually altered contraction.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, we suggest that the most targeted approach to “rescuing” either HCM or DCM phenotype would be to have a mutation within that same domain to counteract manifestation of the disease, probably through TnT1’s flexibility and eventually altered contraction. The increased binding affinity between R141W troponin and Tm [31] possibly underlies the increased cooperativity of thin filament activation displayed by the HET mice within this study (Table 1). Interestingly, I79N/HET mice displayed a normalization of cooperativity of thin filament activation (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…When cooperative stabilization between neighboring RUs is decreased by TnT F88L , it decreases the threshold for Ca 2+ to activate RUs, leading to increased Ca 2+ sensitivity of thin filaments. Such attenuation of RU–RU cooperativity may result from the weakening of TnT–Tm interactions ( Gangadharan et al, 2017 ) and/or an effect on Tm–Tm overlap junction; in theory, this would lower the effective stiffness of the Tm chain and decrease cooperative communication between RUs. This line of reasoning is consistent with previous findings that have suggested that one primary mechanism by which HCM-linked thin filament mutations enhance myofilament Ca 2+ sensitivity is through attenuation of RU–RU cooperativity ( Palm et al, 2001 ; Hinkle and Tobacman, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both may play roles [ 119 , 120 , 121 ] in controlling the degree to which myosin heads leave their sequestered (parked) super-relaxed state [ 40 , 41 ] on the thick filaments under different conditions, e.g., in case of stress or need for increased power. These properties are of increasing interest to study using in vitro systems with isolated proteins because of potentially important roles in effects of myosin active drugs [ 21 , 24 , 40 , 122 ] and/or in cardiomyopathies [ 30 , 31 , 38 , 123 , 124 , 125 , 126 , 127 ]. In these regards the degree of phosphorylation of the regulatory light chains of striated muscle myosin is also of interest to control as this property affects both the state of activation of the thick filaments and drug effects [ 38 , 128 , 129 , 130 , 131 , 132 , 133 ].…”
Section: Challenges In Single-molecule Mechanicsmentioning
confidence: 99%